A Dimeric Chromium(II) Pincer as an Electron Shuttle for N=N Bond Scission. Issue 61 (30th September 2020) - Labrum, Nicholas S.; Cabelof, Alyssa C.; Caulton, Kenneth G.
Abstract: Reduction of the bis‐pyrazolyl pyridine complex [CrL]2 with 4 KC8, followed by addition of one azobenzene (overall mole ratio 1:4:1), PhNNPh, transfers reducing equivalents to three azobenzenes, to form [K3 Cr(PhNNPh)3 ]. This has three κ 2 PhNNPh 2− ligands and K + bound to nitrogen atoms of azobenzene. When the stoichiometry is modified to 1:4:3, the product is changed to [K2 CrL(PhNNPh)2 ], which has C 2 symmetry except for the intimate ion pairing of two K + ions to reduced azobenzene nitrogen atoms, and to pyrazolate and phenyl rings. The origin of the observed delivery of reducing equivalents to several, not to a single N=N bond, is traced to the resistance of the one‐electron‐reduced substrate to receiving a second electron, and is thus a general phenomenon. [CrL]2 alone is shown to be a two‐electron reductant towards benzo[ c ]cinnoline (BCC) resulting in a product of formula [Cr2 L2 (BCC)], in which the reducing equivalents originate purely from Cr II . An analogous study of the reaction of [CrL]2 with azobenzene yields [Cr2 L2 (PhNNPh)(THF)], an adduct in which one THF has displaced one of four hydrazide nitrogen/Cr bonds. Together these illustrate different modes for the Cr2 L2 unit to bind and reduce the N=N bond. Collectively, these results show that two divalent Cr, without added K 0, have the ability to reduce the N=N bond. Further KC8 reduction of preformed Cr2 L2 (RNNR) inevitably gives products in which K + stabilizes the charge in the increasingly electron‐rich nitrogen atoms, in a phenomenon which mimics proton coupled electron transfer: K + performs the role of H + . A least‐squares fit of the two singly reduced DFT structures shows that the only major change is a re‐orientation of one of the two phenyl rings in order to avoid repulsion with potassium but to still allow interaction of that phenyl π system with K + . This shows both the impact of K +, being modest to nitrogen/chromium interactions, but nevertheless accommodating some π donation of phenyl to potassium. Finally, delivering increasing equivalents of KC8 leads to complete cleavage of the N=N bond, and both N bind to three Cr II . The varied impacts of the K + electrophile on NN multiple bond reduction is discussed. Abstract : Coordination modes : The ability of two divalent Cr, contained in the compact molecule [CrL]2, to reduce N=N bonds in azobenzene and benzo[ c ]cinnoline resulting in Cr2 L2 (RNNR) is reported (see figure). Additional reduction of Cr2 L2 (RNNR) with KC8 gives products in which K + stabilizes the charge in the increasingly electron‐rich nitrogen atoms. This phenomenon mimics proton‐coupled electron transfer (PCET): K + performs the role of H + .